Caras: Semana de la Raza (MECHA)
Today, we have gathered here at Occidental College to celebrate the anniversary of the 5th of May of 1862, when in Puebla, our people struck the first blow against the French to liberate themselves from the foreign domination that had gained control of Mexico by force.